Implementation of Permendikbudristek Number 30 of 2021 And The Law on The Criminal Action of Sexual Violence Towards The Behavior of Sexual Harassment by Educators To Students In The Campus Environment (Case Study of The University of Muhammadiyah Tangerang) - Efrilia, Erma; Fauziah Ahmad, Dwi Nur; Amiludin, Amiludin; Hidayatullah, Hidayatullah (JUSTITIA JURNAL HUKUM, 2023)
Sexual harassment has recently occurred a lot in the campus environment, the purpose of this study is to find out the application of Regulation of the Minister of Education, Culture, Research and Technology number 30 of 2021 and the law on criminal acts of sexual violence against sexual harassment behavior by educators to students in the University Muhammadiyah Tangerang environment, this research is empirical juridical with primary and secondary data sources, primary data is obtained from interviews with speakers, namely the director of Legal Aid of University Muhammadiyah Tangerang, Taskforce and student selection committee, observations in the University Muhammadiyah Tangerang campus environment and documentation, while the secondary data comes from primary legal materials in the form of laws and regulations, namely Regulation of the Minister of Education, Culture, Research and Technology number 30 of 2021 and Law Number 12 of 2022 concerning sexual violence crimes, which is then analyzed qualitatively so that data is presented in the form of sentences. The result of the discussion was the existence of a task force selection committee as a form of implementing regulations and protecting victims.Sexual harassment, campus, implement, regulations